A Family of Energetic Materials Based on 1,2,4-Oxadiazole and 1,2,5-Oxadiazole Backbones With Low Insensitivity and Good Detonation Performance - Xue, Qi; Bi, Fu-qiang; Zhang, Jun-lin; Wang, Zi-jun; Zhai, Lian-jie; Huo, Huan; Wang, Bo-zhou; Zhang, Sheng-yong (Frontiers in Chemistry, 2020)
Design and synthesis of new compounds with both high detonation performances and good safety properties have always been a formidable task in the field of energetic materials. By introducing -ONO2, -NHNO2 moieties into 1,2,4-oxadiazole- and 1,2,5-oxadiazole-based backbones, a new family of energetic materials, including ammonium 3-nitramino-4-(5-hydroxymethyl-1,2,4-oxadiazol-3-yl)-furazan (4), 3,3'-bis[5-nitroxymethyl-1,2,4-oxadiazol-3-yl]-4,4'-azofuroxan (6), [3-(4-nitroamino-1,2,5-oxadiazol-3-yl)-1,2,4-oxadiazol-5-yl]-methylene nitrate (8) and its energetic ionic salts (10-12), were synthesized and fully characterized. The energetic and physical properties of the materials were investigated through theoretical calculations and experimental determination.The results show that the oxadiazole-based compounds exhibit high enthalpy of formations, good detonation performances and extraordinary insensitivities. In particular, the hydrazinium salt (11) shows the best energetic properties (11: d =1.821 g cm-3; P = 35.1 GPa, vD = 8822 m s-1, IS = 40 J, FS > 360 N). The ESP and Hirshfeld surfaces analysis indicated that a large number of hydrogen bonds as well as π-π stacking interacions within molecules might be the key reason for their low sensitivities and high energy-density levels